Finite element analysis predicts experimental failure patterns in vertebral bodies loaded via intervertebral discs up to large deformation. Issue 6 (June 2015) - Clouthier, Allison L.; Hosseini, Hadi S.; Maquer, Ghislain; Zysset, Philippe K.
Highlights: A nonlinear FE model with intervertebral discs was created for two spine segments. Spine segments were tested experimentally in stepwise loading to large compression. The model correctly predicted bone compaction and fracture locations. Healthy disc, degenerated disc and embedded endplates were compared. Embedded endplates were unable to replicate endplate fractures. Abstract: Vertebral compression fractures are becoming increasingly common. Patient-specific nonlinear finite element (FE) models have shown promise in predicting yield strength and damage pattern but have not been experimentally validated for clinically relevant vertebral fractures, which involve loading through intervertebral discs with varying degrees of degeneration up to large compressive strains. Therefore, stepwise axial compression was applied in vitro on segments and performed in silico on their FE equivalents using a nonlocal damage-plastic model including densification at large compression for bone and a time-independent hyperelastic model for the disc. The ability of the nonlinear FE models to predict the failure pattern in large compression was evaluated for three boundary conditions: healthy and degenerated intervertebral discs and embedded endplates. Bone compaction and fracture patterns were predicted using the local volume change as an indicator and the best correspondence was obtained for the healthy intervertebral discs. These preliminary results show that nonlinear finite element models enable prediction of bone localisation and compaction. To the best of our knowledge, this is the first study to predict the collapse of osteoporotic vertebral bodies up to large compression using realistic loading via the intervertebral discs. Graphical abstract: